1987
DOI: 10.1073/pnas.84.19.6730
|View full text |Cite
|
Sign up to set email alerts
|

A cis-acting element is necessary and sufficient for translational regulation of human ferritin expression in response to iron.

Abstract: Ferritin plays a key role in determining the intracellular fate of iron and is highly regulated by the iron status of the cell. We have identified a cis-acting element in the transcribed but nontranslated 5' leader sequence of human ferritin heavy-chain mRNA. In transiently transfected murine fibroblasts, the presence of a 157-nucleotide region of the 5' leader sequence was found to be necessary for iron-dependent regulation of ferritin biosynthesis. Further, this 5' leader region is sufficient to transfer iro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
112
0
1

Year Published

1988
1988
2016
2016

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 232 publications
(119 citation statements)
references
References 28 publications
6
112
0
1
Order By: Relevance
“…Early evidence suggested that the primary site of this regulation may be translational (4)(5)(6)(7)(8)(9). This has been confirmed recently by the discovery of the "iron-responsive element" (IRE), a highly conserved sequence of 28 nucleotides, in the 5' untranslated region (5' UTR) of all ferritin mRNAs (10)(11)(12)(13). The presence of this sequence renders the translation of downstream open reading frames (ORFs) responsive to the iron status of the cell.…”
mentioning
confidence: 75%
“…Early evidence suggested that the primary site of this regulation may be translational (4)(5)(6)(7)(8)(9). This has been confirmed recently by the discovery of the "iron-responsive element" (IRE), a highly conserved sequence of 28 nucleotides, in the 5' untranslated region (5' UTR) of all ferritin mRNAs (10)(11)(12)(13). The presence of this sequence renders the translation of downstream open reading frames (ORFs) responsive to the iron status of the cell.…”
mentioning
confidence: 75%
“…Ferritin transcripts are stored in an untranslated ribonuclear pool and shifted to polyribosomes as the protein is needed. The 5' untranslated leader sequence of ferritin mRNA confers the translational regulatory property to a heterologous gene in a transformation assay (13,14). Similarly, it may be possible to identify regions in the well-characterized Sh gene (27) that are responsible for the translational control of SS I transcripts during anaerobic stress.…”
Section: Chase Of [35s]met With Unlabeled Methioninementioning
confidence: 99%
“…Simultaneously, the binding of IRPs to IRE cis-element in the 5'-UTR of ferritin mRNA prevents its synthesis [14,15]. On the other hand, high iron levels reduce IRPs affinity to IREs (i.d.…”
Section: Introductionmentioning
confidence: 99%